The Effect of Calcium Chloride on Anti-Xa Activity of Heparin and Its Molecular Weight Fractions - Barrowcliffe, T W; Shirley, Yvonne Le (Thrombosis and Haemostasis, 1989)
The anti-Xa activities of unfractionated heparin (UFH) and nine low molecular weight heparins (LMWH) have been measured in the presence and absence of 3 mM CaCl2, using bovine Factor Xa, purified human AT III and an amidolytic assay. The addition of CaCl2 increased the activity of UFH by 93%, but the effect on LMWH was less, ranging from −20% to +55%. Studies of gel filtration fractions of UFH showed marked Mr dependence of the CaCl2 effect in the range 4,000-12,000. The differences among the various LMW heparins with respect to the effect of CaCl2 were closely correlated with the amount of polysaccharide above an Mr of 6,500. Kinetic studies confirmed the potentiation of the activity of UFH with bovine Xa and showed an even more marked effect using human Xa.
Keywords: Heparin; LMW heparin; Anti-Xa